Teacher Educator’s Qualities for Successful Teaching: Students’ Perspectives on Teacher’s Personal Traits in Nepalese Context - Mouni, Ram Bahadur (Journal of Durgalaxmi, 2022)
The nature of teacher education in Nepal is being questioned by various critics because they argue that it only focuses on the formal or theoretical knowledge of the teachers rather than considering practical and behavioral aspects of teachers’ professional development. On this ground, this phenomenological research primarily aims at identifying students’ perspectives on personal qualities/characteristics of teacher educators and investigating how such personal qualities/characteristics contribute to successful teaching in the context of Nepal. The data has been collected through personal and structured interview taken with 10 students (who are prospective teachers as well) purposively selected from the 5 campuses of Kailali district that run B. Ed. and M. Ed. Programs. Through the interpretation and analysis of the data, the study reveals that personal characteristics of teacher educators are essential for successful teaching and learning. Such qualities should be recognized as the formal parameters of assessing teacher’s qualification for improving the entire course of teacher education.